Calving Induced Speedup of Petermann Glacier. Issue 1 (26th January 2019) - Rückamp, Martin; Neckel, Niklas; Berger, Sophie; Humbert, Angelika; Helm, Veit
Abstract : This study assesses the response on ice dynamics of Petermann Glacier, a major outlet glacier in northern Greenland, to the 2012 and a possible future calving event. So far Petermann Glacier has been believed to be dynamically stable as another large calving event in 2010 had no significant impact on flow velocity or grounding line retreat. By analyzing a time series of remotely sensed surface velocities, we find an average acceleration of 10% between winter 2011/2012 and winter 2016/2017. This increase in surface velocity is not linear but can be separated into two parts, starting in 2012 and 2016 respectively. By conducting modeling experiments, we show that the first speedup can be directly connected to the 2012 calving event, while the second speedup is not captured. However, on recent remote sensing imagery newly developing fractures are clearly visible ∼12 km upstream from the terminus, propagating from the eastern fjord wall to the center of the ice tongue, indicating a possible future calving event. By including these fracture zones as a new terminus position in the modeling domain, we are able to reproduce the second speedup, suggesting that surface velocities remain on the 2016/2017 level after the anticipated calving event. This indicates that, from a dynamical point of view, the terminus region has already detached from the main ice tongue. Key Points: Based on remote sensing data, Petermann Glacier sped up after the calving event in 2012 Speedup is caused by a reduction in buttressing Further retreat into the fjord likely causes glacier acceleration